Improving the IEA Approach Using Principles of Open Data Science. Issue 1 (9th November 2020) - Bastille, Kimberly; Hardison, Sean; deWitt, Lynn; Brown, Jennifer; Samhouri, Jameal; Gaichas, Sarah; Lucey, Sean; Kearney, Kelly; Best, Ben; Cross, Scott; Large, Scott; Spooner, Ellen
Abstract: Integrated ecosystem assessments (IEAs) compile and use indicators, risk assessments, and other analyses to address regional policy needs at varying spatial scales. Although approaches to implementing IEAs are context-specific, challenges in data acquisition, management, processing, analysis, and communication are universal. By embracing open science, in which scientific data, methods, and products are made publicly accessible, along with the ever-expanding tools facilitating open science, IEA practitioners will be better equipped to address these challenges. Here, we provide a snapshot of the state of open science practices in IEAs on-going across the United States. We show that open science has improved the flexibility, reproducibility, and efficiency of the scientific workflows within the IEA framework. Although the initial time investment necessary for developing open science workflows may appear daunting, we show that the subsequent returns provided by the efficient and transparent development of IEA products are worth the effort. By improving the implementation of IEAs, open science tools and principals have the potential to further Ecosystem Based Management (EBM) worldwide.